The CORRELATION BETWEEN FAMILY SUPPORT AND ADHERENCE TO ROUTINE CONTROLLING TREATMENT IN PATIENTS WITH TYPE 1 DIABETES MELLITUS I IN MERAUKE - Ratnawati -; Nurmah Rachman; Wibowo Hanafi; Qoriah Nur; santalia Banne Tondok* (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2022)
Objective: To determine the correlations between family support and adherence to routine control of type 1 diabetes mellitus patients at the Internal Policlinic of Merauke Hospital. Methods: The design of the research is cross-sectional. The number of samples was 45 people with type 1 diabetes mellitus with inclusion and exclusion criteria. This study's data analysis used an alternative test of the fisher exact test because the chi-square test did not meet the requirements. After all, the number of samples was small. Results: The results showed a relationship between family support and adherence to common control in patients with type 1 diabetes mellitus at the Internal Policlinic of Merauke Hospital with a p-value = 0.002 (p < 0.05). It can be seen that 45 respondents received good family support, as many as 36 respondents (80 %), while those who obeyed routine control 38 respondents (84.4 %). Family support can improve compliance with controlling patients with type 1 DM routinely at the Internal Policlinic of Merauke Hospital. Conclusion: There is a significant correlation between family support and compliance with routine control in patients with type 1 diabetes mellitus at the Internal Policlinic of Merauke hospital.